Factors associated with food safety behavior of members in the Village Food Security Movement Program in Bolaang Mongondow Regency, Indonesia - Kusumawardani, Dian Sulistyaning; Kapantow, Nova Hellen; Djarkasi, Gregoria Sri Suhartati (YCAB Publisher & IAKMI SULTRA, 2022)
Background: Food safety is the aspect considered to prevent food poisoning worldwide. Food safety management is essential to prevent foodborne illness. Objective: This study aimed to determine factors associated with the food safety behavior of members in the Village Food Security Movement Program in Bolaang Mongondow Regency, Indonesia. Methods: Cross-sectional research was conducted on 100 participants through a purposive sampling technique in the last week of February 2022 with the COVID-19 protocol. Data were collected using validated questionnaires. Descriptive statistical tests, Chi-square test, and multi-logistic regression were employed for data analysis. Results: The majority of the respondents were female (65%) and 15-59 years old. The Chi-square analysis found education, knowledge, and attitude were significant variables. After adjusting to the multi-logistic regression, the poor attitude and low cost of family food consumption were associated with poor food safety behavior (p <0.05). Conclusion: The most significant factors related to poor food safety behavior are the low cost of family food consumption and low attitude. The program must be appropriately arranged to prevent poor food safety behavior in the households.